Dervishes and Islam in Bosnia : sufi dimensions to the formation of Bosnian Muslim society - Aščerić-Todd, Ines. (The Ottoman Empire and its Heritage, 2015)
In Dervishes and Islam in Bosnia , Ines Aščerić-Todd explores the involvement of Sufi orders in the formation of Muslim society in the first two centuries of Ottoman rule in Bosnia (15th - 16th centuries C.E.). Using a wide range of primary sources, Aščerić-Todd shows that Sufi traditions and the activities of dervish orders were at the heart of the religious, cultural, socio-economic and political dynamics in Bosnia in the period which witnessed the emergence of Bosnian Muslim society and the most intensive phase of conversions of the Bosnian population to Islam. In the process, she also challenges some of the established views regarding Ottoman guilds and the subject of futuwwa (Sufi code of honour).